Nutritional values of Avicennia marina leaves and its application as fodder for Kacang goat (Capra aegagrus) - MOHAMMAD BASYUNI; MUHAMMAD RISKY RIZALDI; RIZKA AMELIA; YUNTHA BIMANTARA; NURDIN SULISTIYONO; BEJO SLAMET; SHOFIYAH SABILAH AL MUSTANIROH (Society for Indonesian Biodiversity, 2023)
Abstract. Basyuni M, Rizaldi MR, Amelia R, Bimantara Y, Sulistiyono N, Slamet B, Al Mustaniroh SS. 2023. Nutritional values of Avicennia marina leaves and its application as fodder for Kacang goat (Capra aegagrus). Biodiversitas 24: 1039-1048. Mangrove forests provide a variety of ecosystem services including provisioning and cultural services in which coastal communities traditionally utilize mangrove plants to support their daily life. There are several practices on the uses of mangrove foliage for animal feed by coastal communities, although it is not clear the nutritional value of such feed source and its effect on livestock growth. This study aimed to determine the potential use of Avicennia marina leaves as fodder for Kacang goat (Capra aegagrus) by investigating the nutritional values in terms of proximate contents and macro- and micro-elements of A. marina leaves and the effects of the feeding A. marina leaves on the dimensional growth of Kacang goat in term of chest circumference, body length and body weight. We employed two treatments (i.e. fodder of A. marina leaves and field grass for the comparison) with three replicates for each treatment. The results showed that the leaves of A. marina had a higher content of crude fat, carbohydrates, EWN (extract without nitrogen) and vitamin C, and lower content of water, ash, crude protein, and crude fiber compared to field grass. In terms of macro and microelements, A. marina leaves had a higher level of Ca and Na, but lower in terms of P, K, S, Fe, Zn, Cu and Mn. Nonetheless, feeding Kacang goat with A. marina leaves resulted in a significantly lower daily body weight gain (16.08 g/goat/day) compared to feeding with field grass (74.46 g/goat/day). During the observation period of 92 days, feeding with field grass increased body weight by 6.85 kg, higher than feeding with A. marina leaves, which caused a weight gain of 2.22 kg. Furthermore, the average feed conversion for field grass treatment was 5.24 (g consumption/g daily body weight gain/DWG) while feed of A. marina leaves was 4.42 (g consumption/g DWG), indicating inefficient use of feed. The dry weight content of FG feed (149.39%) was slightly higher than that of A. marina leaves (149.24%). This study provides evidence of the possibility of the application of A. marina leaves as the fodder for Kacang goat.